IMPROVING STUDENTS’ READING SKILL THROUGH INTERACTIVE APPROACH AT THE FIRST GRADE OF SMAN 1 MARE, BONE - Andi Herdiana Nur; Djuwairiah Ahmad (Universitas Islam Negeri Alauddin Makassar, 2017)
This paper aims to find out the improvement of the students’ reading skill at the First grade of SMAN 1 Mare Bone through Interactive Approach method. This research used classroom action research (CAR) which was conducted to solve the students’ problem in English reading. The Classroom Action Research (CAR) was done based on Kemmis and McTaggart’s design.the researcher did two cycle in which each cycle consists of planning, acting, observing, and reflecting. The finding of the research indicated that the implementation Interactive Approach was successful since the criteria of success were achieved. The first criterion was 70 % of students could pass the target score 70 based on the KKM. The finding showed that 74.57 of students had already achieved the target score. besides, the second criterion was the students who become more active involved in teaching learning process. the result of observation checklist showed that through Interactive Approach method, the students were more creative confident in the classroom especially reading activity. Based on the finding mentioned above, the researcher suggest that English teacher could implement Interactive Approach method in teaching reading in order to improve students in learning Englsih reading.